The Effect of Concentration of Tofu Liquid Waste POC on the Growth of Pakchoy Plants (Brassica rapa L.) - Ipung/Riza, Syaifur riza; Umi Kulsum Nur Qomariah; Faizah, Mazidatul (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
The purpose of the reasearch to determine the effect of Organic fertilizer in liquid form (POC) from liquid waste from tofu on pakcoy plants. The study was conducted in September - December 2025 in an experimental garden located in Pandean Hamlet, Ngoro Village, Ngoro, Jombang. This study employed a quantitative approach with a Completely Randomized Design (CRD). This approach uses five treatments, namely P0 (Control Soil), P1 (Provision of 25% tofu liquid waste POC), P2 (Provision of 35% tofu liquid waste POC), P3 (Provision of 45% tofu liquid waste POC). Some parameters of pakcoy plants are plant height, number of leaves, root volume, growth rate, and plant fresh weight. The results of the study showed that from the results of ANOVA, plant height was known to be Fhit (1.68) < F5% (2.86), number of leaves was known to be Fhit (1.21) < F5% (2.86), root volume (1.19) < F5% (2.86), fresh weight was known to be Fhit Fhit (1.88) < F5% (2.86), growth rate was known to be Fhit (1.60) < F5% (2.86) meaning that liquid organic fertilizer of Moringa leaves had no effect on these 4 parameters.